Analysis of factors associated with multiple ventilation tube insertions in children with otitis media with effusion. Issue 4 (29th March 2019) - Choi, H; Lee, D; Hong, Y; Kim, D-K
Abstract: Objective: To determine the factors related to multiple ventilation tube insertions in children with otitis media with effusion. Methods: A retrospective review was performed of 126 ears of 81 children aged less than 12 years who had undergone insertion of a Paparella type 1 ventilation tube for the first time between August 2012 and March 2018. Results: Mean age at the first operation was 4.0 ± 2.2 years, and the mean duration of otitis media with effusion before the first ventilation tube insertion was 5.4 ± 4.5 months. Among 126 ears, 80 (63.5 per cent) had a single ventilation tube insertion and 46 (36.5 per cent) had multiple insertions. On multivariate logistic regression, tympanic membrane retraction, serous middle-ear discharge, and early recurrence of otitis media with effusion were independent predictive factors of multiple ventilation tube insertions. Conclusion: Tympanic membrane retraction, serous middle-ear discharge, and early recurrence of otitis media with effusion after the first tube extrusion are associated with multiple ventilation tube insertions.